DESIGNING CHILDREN’S CREATIVITY AND DIAGNOSTIC ANALYSIS OF THEIR DEVELOPMENT. - O. Shodiyeva (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article gives an idea of ​​the degree to which children's musical abilities are formed, and how music lessons in preschool institutions form children's musical abilities through various activities in the process of a music lesson. It also provides a brief overview of the diagnostic analysis of children's creative development through music education.